Poverty in Tunisia: A Fuzzy Measurement Approach - Besma Belhadj; Mohamed Salah Matoussi (Swiss Journal of Economics and Statistics, 2010)
Although poverty is widely recognised as a multidimensional phenomenon, we still believe that monetary aspect has a fundamental role and therefore deserves a special treatment. For this reason we propose an individual unidimensional measure according to a fuzzy approach that, unlike conventional methods, is consistent with the vague nature of poverty and preserves all the available statistical information. Referred to the overall population, we use an Information Theory approach to design unidimensional fuzzy collective index. The methodology proposed here is illustrated by means of the Tunisia case.
Keywords: P46; I32; D81; 330; fuzzy sets; poverty; poverty line; membership function; information function